Izbrani primeri iz novejše sodne prakse Vrhovnega sodišča Republike Slovenije na področju delovnih in socialnih sporov - Debelak, Marijan (Delavci in delodajalci, 2020)
In his paper, the author summarizes some examples from the case law of the Supreme Court of the Republic of Slovenia in the first half of 2020 in individual and collective labor and social disputes. The selection of cases is limited to some of the most interesting audit matters.
Keywords: accident at work; annual leave; Center of Social Work; center za socialno delo; compensation; disability; dismissal; education and training; harassment at work; invalidnost; izobraževanje in usposabljanje; letni dopust; managers; nesreče pri delu; odpoved; odškodnine; poslovodne osebe; reprezentativnost sindikata; sindikalni zaupnik; trpinčenje na delovnem mestu; union representativeness; union trustee